PENGARUH INVESTASI AGRO INDUSTRI DAN TINGKAT SUKU BUNGA SERTA TENAGA KERJA TERHADAP PRODUK DOMESTIK REGIONAL BRUTO DAN PENDAPATAN ASLI DAERAH KOTA SAMARINDA - Maria, Siti (Faculty of Economics and Business, University of Muhammadiyah Malang, 2014)
The purpose of this study are to determine the effect of agro industry Investment, interest rate, and labor toward gross regional domestic product (GRDP) and regional revenues in Samarinda city; and to describe the effect of gross regional domestic product (GRDP) toward the regional revenues in Samarinda City. The data analyzing used in this study is regressions in two ways. Based on the result, the researcher found that: first, the variable of agro industry investment, interest rate, and the amount of labor had significant effect toward regional domestic product (GRDP) in Samarinda city; Second, the variable of agro industry investment, interest rate, the amount of labor, and regional domestic product (GRDP) had significant effect toward regional revenues in Samarinda City; and third, gross regional domestic product (GRDP) was proved significantly affecting regional revenues in Samarinda city.